2022
DOI: 10.1111/acel.13602
|View full text |Cite
|
Sign up to set email alerts
|

Targeted clearance of p21‐ but not p16‐positive senescent cells prevents radiation‐induced osteoporosis and increased marrow adiposity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…Surprisingly, p16INK4A- and p21-expressing cell populations seem to be different [ 212 ], which is contrasting with the lack of senescence in p16INK4A/p21 double knockout animals [ 251 ]. Also in the p21–ATTAC model, the clearance of p21- but not p16INK4A-positive senescent cells prevented radiation-induced osteoporosis and bone marrow adiposity [ 226 ], supporting the view that p16INK4A- and p21-dependent senescence comprise different and independent pathways [ 3 , 5 , 22 , 273 ]. A high number of p21- but not p16INK4A-expressing cells was detected in visceral adipose tissue of obese mice, mostly preadipocytes, endothelial cells, and macrophages [ 218 ].…”
Section: P16ink4a P14arf/p19arf and P21 In Homeostasismentioning
confidence: 87%
See 1 more Smart Citation
“…Surprisingly, p16INK4A- and p21-expressing cell populations seem to be different [ 212 ], which is contrasting with the lack of senescence in p16INK4A/p21 double knockout animals [ 251 ]. Also in the p21–ATTAC model, the clearance of p21- but not p16INK4A-positive senescent cells prevented radiation-induced osteoporosis and bone marrow adiposity [ 226 ], supporting the view that p16INK4A- and p21-dependent senescence comprise different and independent pathways [ 3 , 5 , 22 , 273 ]. A high number of p21- but not p16INK4A-expressing cells was detected in visceral adipose tissue of obese mice, mostly preadipocytes, endothelial cells, and macrophages [ 218 ].…”
Section: P16ink4a P14arf/p19arf and P21 In Homeostasismentioning
confidence: 87%
“…The second mouse strain is comparable to the p16INK4A-INK-ATTAC mouse model but uses a 3.2 kb p21 promoter fragment driving expression of the FKBP–Caspase-8 fusion suicide protein. The construct was inserted in the Rosa26 locus [ 226 ]. The p21-CreERT2 mice were crossed with a luciferase reporter, and luminescence was measured in vivo after doxorubicin treatment or a high-fat diet as known inducers of senescence.…”
Section: P16ink4a P14arf/p19arf and P21 In Homeostasismentioning
confidence: 99%
“…Regarding senescence, the relative contributions of different senescence-inducing pathways to specific age-related diseases remain undetermined. A very recent study showed that radiation-induced osteoporosis in mice is mainly driven by p21 CIP1 SCs rather than SCs expressing p16 INK4 and that eliminating p21 + , but not p16 + , cells ameliorates this pathology (133). These comparative mouse models should be used by future research to associate specific senescence pathways with organ-specific aging outcomes, which will help rationalize the use of specific biomarkers over others.…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…Recent reports show that cells expressing high levels of p21 in vivo express other markers of senescence and their numbers increase with age, in multiple murine organs [11]. In addition, elimination of p21 + senescent cells reduces frailty and attenuates insulin resistance in obese mice [12], while elimination of p21 + cells, but not p16 + cells, improves radiation-induced osteoporosis [13],…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports show that cells expressing high levels of p21 in vivo express other markers of senescence and their numbers increase with age, in multiple murine organs [11]. In addition, elimination of p21 + senescent cells reduces frailty and attenuates insulin resistance in obese mice [12], while elimination of p21 + cells, but not p16 + cells, improves radiation-induced osteoporosis [13], suggesting that p21 is a good marker of senescent cells. Zebrafish have a homologue of the human p21 gene, known to increase with increased levels of p16-like expression and senescence associated beta-galactosidase [14].…”
Section: Introductionmentioning
confidence: 99%